Relationship Between Self-belief With Enterprise Interest Graduates of Beauty Training - Rahmi Yusnedi; Solfema Solfema (Universitas Negeri Padang, 2020)
This study aims to reveal an overview of the confidence of training graduates, and to reveal the relationship between self-confidence and entrepreneurial interest in beauty training graduates at the Training and Training Institute (LKP) Martha Siska Padang. The results of the observations show that the low interest in entrepreneurship is thought to be caused by a lack of self-confidence from beauty training graduates. This type of research is a correlational study that uses a quantitative approach. The population in this study were graduates of beauty training for the period 2019. The sampling technique was saturated sampling and the sample was the entire population. The data collection technique used was a questionnaire and the tools used were a questionnaire. The data analysis technique used the percentage formula and the Spearman Rho formula. The results of this study indicate that: 1) the confidence of training graduates is low; 2) training graduates have low interest in entrepreneurship;3) There is a significant relationship between self-confidence and entrepreneurial interest in beauty training graduates at LKP Martha Siska, Padang City. Suggestions from this research are that training graduates are expected to be confident in their potential, and institutional managers are expected to generate self-confidence and entrepreneurial interest from beauty training trainees, as well as increase knowledge of trainees about self-confidence and interest in entrepreneurship. in practice it has been done well.Keywords: self-confidence, interest in entrepreneurship